PENGENALAN LINGKUNGAN PESISIR DAN LAUT BAGI SISWA SMP NEGERI 1 ATAP SATHER, KABUPATEN MALUKU TENGGARA - Hukubun, Wiwien Gaby; Huwae, Laury Marcia Chara (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2022)
Coastal villages have direct access to coastal ecosystems, mangroves, seagrass beds, and coral reef ecosystems. Socio-ecologically, coastal villages have a linkage and dependence between coastal community activities and the existence of ecosystems/ecology. Knowledge of coastal areas is important for the people living around the area. Community Service is focused on teenagers/youth as part of the community with an educative counseling approach to the students of SMP Negeri Satu Atap Sather which aims to foster a sense of love and care for the coastal area and the ecosystem in it. Service activities went well. More intense and periodic education is needed to instill a caring attitude and a sense of love for the coastal and marine environment, so that coastal and marine resources can be maintained and sustainable